2012
DOI: 10.1007/s12253-012-9523-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression of BAG-1 and PARP-1 in Precursor Lesions and Invasive Cervical Cancer Associated with Human Papillomavirus (HPV)

Abstract: Cervical cancer remains persistently the second most common malignancies among women worldwide, responsible for 500,000 new cases annually. Only in Brazil, the estimate is for 18,430 new cases in 2011. Several types of molecular markers have been studied in carcinogenesis including proteins associated with apoptosis such as BAG-1 and PARP-1. This study aims to demonstrate the expression of BAG-1 and PARP-1 in patients with low-grade squamous intraepithelial lesions (LSILs), high-grade squamous intraepithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Notably, the present study similarly demonstrated that PARP-1 expression levels were significantly increased in H. pylori infected gastric cancer cells. Regarding pathogenic infection, Hassumi-Fukasawa et al (51) demonstrated a significant positive association between PARP-1 expression levels and human papilloma virus positivity, in high-grade squamous intraepithelial lesions of the uterine cervix. Therefore, PARP-1 expression levels may be involved in host cell responses to pathogen infection.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the present study similarly demonstrated that PARP-1 expression levels were significantly increased in H. pylori infected gastric cancer cells. Regarding pathogenic infection, Hassumi-Fukasawa et al (51) demonstrated a significant positive association between PARP-1 expression levels and human papilloma virus positivity, in high-grade squamous intraepithelial lesions of the uterine cervix. Therefore, PARP-1 expression levels may be involved in host cell responses to pathogen infection.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, PARP-1 was easily detected by immunohistochemistry in 86%, 77.5%, and 94% of patients with low-grade SIL (50 samples), high-grade SIL (HSIL, 50 samples), and invasive squamous cell carcinoma (SCC, 50 samples), respectively. 7 In the HSIL group, HPVpositive cells seem to express PARP-1 to a higher degree than HPV-negative cells. Moreover, in invasive cancer tissues, a significantly higher immunostaining of PARP-1 compared with HSIL was found (P = 0.001).…”
Section: Parp-1 Expression In Cervical Precancer and Cancermentioning
confidence: 89%
“…In a study by Hassumi-Fukasawa et al, 7 the immunohistochemical staining of normal cervical tissues revealed no PARP-1 expression or only light staining in the areas of the basal and parabasal layer cells of the ectocervix. In contrast, PARP-1 was easily detected by immunohistochemistry in 86%, 77.5%, and 94% of patients with low-grade SIL (50 samples), high-grade SIL (HSIL, 50 samples), and invasive squamous cell carcinoma (SCC, 50 samples), respectively.…”
Section: Parp-1 Expression In Cervical Precancer and Cancermentioning
confidence: 94%
See 1 more Smart Citation
“…It has been reported that some viruses associate with the genesis of various benign disorders and some malignant tumours such as cervical cancer (26)(27)(28)(29). Although uterine cervix malignancy is reported to be the fifth most common cancer among Iranian females (30), in many other countries, cervical squamous cell carcinoma is the second most prevalent malignancy (31,32). For a long time, HPV infections have been considered one of the most important aetiological factors in the development of uterine cervix SCC.…”
Section: Discussionmentioning
confidence: 99%